New Frontiers in Entrepreneurship Recognizing, Seizing, and Executing Opportunities - Audretsch, David B.; Dagnino, Giovanni Battista; Faraci, Rosario; Hoskisson, Robert E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
The volume presents and discusses a variety of recent developments and achievements in research on entrepreneurship. It aims at taking a systematic analysis of the theory and practice of entrepreneurship, especially in regard to nurturing strategic systems, governance arrangements, and evolutionary paths in organizations. Bringing together the insights of an international recognized array of academics, entrepreneurs, and executives, New Frontiers in Entrepreneurship focuses on two key themes: (1) connecting developments in entrepreneurship to current strategy thinking and practice; and (2) generating new and innovative ways to cultivate and develop entrepreneurial processes in new ventures and established enterprises. Exploring such topics as the integration of entrepreneurial and strategic thinking, corporate governance of new ventures and spin-offs, business-university alliances, IPO performance, the impact of Open Source, the role of science and technology in new firm formation, and the emergence of the entrepreneurial society. In the process, the authors demonstrate how entrepreneurship promotes organizational genesis, growth, and rejuvenation on a practical level, and consider on the research side how entrepreneurship has developed from a peripheral sub-field of management studies into one of the most relevant spheres of strategic management.
Corporate Governance and Entrepreneurship -- Initially Distracted: The Influence of Boards on Agency Costs in Initial Public Offering (IPO) Firms -- Horizontal and Vertical Relationships in Developing Economies: Implications for SMEs$1 (BAccess to Global Markets -- Corporate Governance Systems: Effects of Capital and Labor Market Congruency on Corporate Innovation and Global Competitiveness -- The Entrepreneurial Society -- Mobilizing Capital for Fostering Entrepreneurship -- Mobilizing Capital for Fostering the Early Growth of Firms: The Role of Business Angels in Nascent European Entrepreneurship -- Venture Capital Financing and the Growth of New Technology-Based Firms: Correcting for Sample Self-Selection -- Learning, Innovation and Entrepreneurship -- Creating Exploratory Innovations by Learning from Entrepreneurial Ventures -- Business-University Alliances and Innovation in New and Adolescent Technology Ventures -- Open Innovation and New Entrepreneurship -- A Test of Lazear$1 (Bs Theory of Entrepreneurship in the Open Source Software Virtual Community -- Open Innovation and the Implications for Sustainable Profits.s
Keywords: Economics; Endogenous growth (Economics).; Entrepreneurship; Economics/Management Science; Entrepreneurship; Business/Management Science, general; Economic Growth